Quorum Quenching-Guided Inhibition of Mixed Bacterial Biofilms and Virulence Properties by Protein Derived From Leaves of Carissa carandas - Shukla, Manjari; Singh, Vineeta; Habeeballah, Hamza; Alkhanani, Mustfa F.; Lata, Manjul; Hussain, Yusuf; Mukherjee, Madhuparna; Pasupuleti, Mukesh; Meena, Abha; Mishra, Bhartendu Nath; Haque, Shafiul (Frontiers in Cellular and Infection Microbiology, 2022)
The inhibition/degradation potential of Carissa carandas proteinaceous leaf extract against mixed bacterial biofilm of Staphylococcus aureus MTCC 96, Escherichia coli MTCC 1304, Pseudomonas aeruginosa MTCC 741, and Klebsiella pneumoniae MTCC 109, responsible for nosocomial infections, was evaluated. Distinct inhibition/degradation of mixed bacterial biofilm by the proteinaceous leaf extract of C. carandas was observed under a microscope, and it was found to be 80%. For mono-species biofilm, the maximum degradation of 70% was observed against S. aureus biofilm. The efficiency of aqueous plant extracts to inhibit the mono-species biofilm was observed in terms of minimum inhibitory concentration (MIC), and the best was found against P. aeruginosa (12.5 μg/ml). The presence of flavonoids, phenols, and tannins in the phytochemical analysis of the plant extract suggests the main reason for the antibiofilm property of C. carandas. From the aqueous extract, protein fraction was precipitated using 70% ammonium sulfate and dialyzed. This fraction was purified by ion-exchange chromatography and found to be stable and active at 10°C (pH 7). The purified fraction showed less than 40% cytotoxicity, which suggests that it can be explored for therapeutic purposes after in-depth testing. In order to investigate the mechanistic action of the biofilm inhibition, the plant protein was tested against Chromobacterium violaceum CV026, and its inhibitory effect confirmed its quorum quenching nature. Based on these experimental analyses, it can be speculated that the isolated plant protein might influence the signaling molecule that leads to the inhibition effect of the mixed bacterial biofilm. Further experimental studies are warranted to validate our current findings.